The loss of autonomy of Nicaraguan universities: five facts for reflection - García Vásquez, Ricardo; Muñoz Reyes, Enrique (Teoría y Praxis, 2024)
The progressive and systematic development of the legalized authoritarian orientation of the government of Daniel Ortega, as of April 2018, has aimed to increase the power of governmental interference and control over the university system, increasing state coverage and enrollment, and subjugating private universities that still remain legalized. This article presents and analyzes documentary and journalistic information regarding the cancellation of legal personalities and confiscation of higher education campuses in Nicaragua, and the reforms to Law No. 89 of 1990 on the Autonomy of Higher Education. The results of this set of processes were verified in five concrete facts: the illegalization of almost three dozen institutions of Higher Education, the effects of the illegalization in the Higher Education subsystem, the proliferation of national universities, the instrumentalization of these new institutions as means of control and political indoctrination, and the reconfiguration of the structure and functions of the National Council of Universities (CNU) from the reforms to Law No. 89 of 1990. In short, this process tends to lead to an absolute loss of Nicaraguan University autonomy.